The politics of law and order: Case study evidence for a conflict model of the criminal law formation process - Castellano, Thomas C. (Journal of research in crime and delinquency, 1991)
An understanding of the origins of crime and justice legislation requires an analysis on three distinct levels. These include the structural foundations, the actual and perceived experience of crime in a social system, and the immediate triggering events of such legislation. In a companion article, we presented an integrative conflict model of the criminal law formation process that incorporates these three levels of analysis. In the present article, we present case study data from contemporary enactments of criminal law in New York State in relation to juvenile justice and gun control. The data suggest that the integrative conflict model does offer heuristic benefits for an understanding of the formation of crime and justice legislation